A Case Study Of Time Dotcom (Time Dotcom Berhad) - Ng, Wei Ping (2008)
Today, the telecommunications industry is in a state of turmoil and the pace of change in this industry is faster than ever before. This industry is becoming less regulated when compared to the previous 10 years. All telecommunications companies are being forced to compete in all aspects.